Urban CO2 Emissions : A Global Analysis with New Satellite Data - Dasgupta, Susmita; Lall, Somik; Wheeler, David (World Bank, Washington, DC, 2021)
This paper estimates an urban carbon dioxide emissions model using satellite-measured carbon dioxide concentrations from 2014 to 2020, for 1,236 cities in 138 countries. The model incorporates the global trend in carbon dioxide concentration, seasonal fluctuations by hemisphere, and a large set of georeferenced variables that incorporate carbon dioxide–intensive industry structure, emissions from agricultural and forest fires in neighboring areas, demography, the component of income that is uncorrelated with industry structure, and relevant geographic conditions. The income results provide the first test of an Environmental Kuznets Curve relationship for carbon dioxide based on actual observations. They suggest an environmental Kuznets curve that reaches a peak near or above $40,000 per capita, which is at the 90th percentile internationally. The research also finds that economic development has a significant effect on the direction of the relationship between population density and carbon dioxide emissions. The relationship is positive at very low incomes but becomes negative at higher incomes. The paper also uses cities’ mean regression residuals to index their carbon dioxide emissions performance within and across regions, decomposes model carbon dioxide predictions into broad source categories for each city, and uses the regression residuals to explore the impact of subway systems. The findings show significantly lower carbon dioxide emissions for subway cities.